Does the quality of life impact of tonsillitis correlate with SIGN guideline compliance? An assessment of range and normality. (15th February 2016) - Roplekar, R.; Van, M.; Hussain, S.S.M.
Abstract : Objectives: To assess the scores of those who are eligible to be listed for tonsillectomy through compliance with the SIGN guidelines for any trends or range. Design: A prospective study of all patients (aged 16 or above) listed for elective tonsillectomy from a nurse led tonsil clinic. Patients were given a TOI‐14 questionnaire to complete after they had been added to the waiting list for surgery, but before undergoing tonsillectomy. Scores were assessed using SPSS. Setting: Outpatient clinic. Participants: Patients aged over 16 listed for Tonsillectomy via SIGN Guideline 117. Main outcome measure: Scores from TOI‐14, completed pre‐operatively. Results: 155 patients were listed from the nurse led clinic from October 2012 to August 2014; 5 questionnaires were excluded for being incomplete. The score range was 55 (15–70), with a calculated mean score of 45.62 and standard deviation of 9.701. Over 95% of results were within 2 standard deviations of the mean. A calculated negative skew also confirms that most patients who have clinical indications for tonsillectomy compliant with the SIGN guidelines show a higher score on the TOI‐14. Conclusion: This analysis indicates a trend of pre‐intervention scores on the TOI‐14 questionnaire for those patients who have a SIGN guideline compliant clinical indication for a tonsillectomy. We therefore propose that this suggests correlation between 'clinically strong' indication for tonsillitis and patient perceived Quality of Life impact.